TikTok sebagai media pembelajaran: Meningkatkan minat belajar bahasa Inggris pada remaja - Widyawati, Rahma Sari Hidayah (Maliki Interdisciplinary Journal, 2024)
The word learning media comes from Latin meaning “medius” which literally means “middle”, intermediary or introduction. Teachers, books, texts, and the school environment are media. In particular, media tend to be defined as graphic, photographic, or electronic tools for capturing, processing, and reconstructing visual and verbal information. Learning media includes tools that are physically used to convey the material content of learning which can be a short video or some kind of game. Learning media is also needed to stimulate interest and motivation to learn for students, besides that learning media also plays a big role in increasing student understanding of a lesson. Social media is a network that allows us to communicate with others. In addition, it is very easy to access through smartphones and computers. Social media also helps us find and learn information. TikTok is one example of social media that we often access to find various information. In today's digital era, it is the target of social media users to be a medium of entertainment, education, and knowledge. The changing times make the internet an unlimited source of learning. It allows people to not only rely on textbooks. Generation Z, or young people, are the biggest users of social media today